Action of Varespladib (LY-315920), a Phospholipase A2 Inhibitor, on the Enzymatic, Coagulant and Haemorrhagic Activities of Lachesis muta rhombeata (South-American Bushmaster) Venom - Gutierres, Pamella G.; Pereira, Diego R.; Vieira, Nataly L.; Arantes, Lilian F.; Silva, Nelson J.; Torres-Bonilla, Kristian A.; Hyslop, Stephen; Morais-Zani, Karen; Nogueira, Rosa M. B.; Rowan, Edward G.; Floriano, Rafael S. (Frontiers in Pharmacology, 2022)
Varespladib (VPL) was primarily developed to treat inflammatory disturbances associated with high levels of serum phospholipase A2 (PLA2). VPL has also demonstrated to be a potential antivenom support agent to prevent PLA2-dependent effects produced by snake venoms. In this study, we examined the action of VPL on the coagulant, haemorrhagic and enzymatic activities of Lachesis muta rhombeata (South-American bushmaster) venom. Conventional colorimetric enzymatic assays were performed for PLA2, caseinolytic and esterasic activities; in vitro coagulant activities for prothrombin time (PT) and activated partial thromboplastin time (aPTT) were performed in rat citrated plasma through a quick timer coagulometer, whereas the dimensions of haemorrhagic haloes obtained after i.d. injections of venom in Wistar rats were determined using ImageJ software. Venom (1 mg/ml) exhibited accentuated enzymatic activities for proteases and PLA2in vitro, with VPL abolishing the PLA2 activity from 0.01 mM; VPL did not affect caseinolytic and esterasic activities at any tested concentrations (0.001–1 mM). In rat citrated plasma in vitro, VPL (1 mM) alone efficiently prevented the venom (1 mg/ml)-induced procoagulant disorder associated to extrinsic (PT) pathway, whereas its association with a commercial antivenom successfully prevented changes in both intrinsic (aPTT) and extrinsic (PT) pathways; commercial antivenom by itself failed to avoid the procoagulant disorders by this venom. Venom (0.5 mg/kg)-induced hemorrhagic activity was slightly reduced by VPL (1 mM) alone or combined with antivenom (antivenom:venom ratio 1:3 ‘v/w’) in rats, with antivenom alone producing no protective action on this parameter. In conclusion, VPL does not inhibit other major enzymatic groups of L. m. rhombeata venom, with its high PLA2 antagonize activity efficaciously preventing the venom-induced coagulation disturbances.